2022
DOI: 10.1101/2022.04.01.22273305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term psychological consequences of long Covid: a propensity score matching analysis comparing trajectories of depression and anxiety symptoms before and after contracting long Covid vs short Covid

Abstract: Background: There is a growing global awareness of the psychological consequences of long Covid, supported by emerging empirical evidence. However, the mergence and long-term trajectories of psychological symptoms following the infection are still unclear. Aims: To examine when psychological symptoms first emerge following the infection with SARS-CoV-2, and the long-term trajectories of psychological symptoms comparing long and short Covid groups. Methods: We analysed longitudinal data from the UCL Covid-19 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Several longitudinal studies on the trajectories of long COVID psychiatric symptoms have shown that some symptoms, such as anxiety, could recover naturally, but some symptoms, particularly depression and cognitive impairments, tend to be chronic [ 8 - 10 , 12 , 24 , 25 ]. Chronic psychiatric sequelae of long COVID are disabling, exerting a long-lasting destructive impact on well-being, quality of life, and educational and occupational functioning, and causing morbidity [ 23 , 26 , 27 ].…”
Section: Clinical Manifestations Of Long Covid Psychiatric Sequelaementioning
confidence: 99%
See 1 more Smart Citation
“…Several longitudinal studies on the trajectories of long COVID psychiatric symptoms have shown that some symptoms, such as anxiety, could recover naturally, but some symptoms, particularly depression and cognitive impairments, tend to be chronic [ 8 - 10 , 12 , 24 , 25 ]. Chronic psychiatric sequelae of long COVID are disabling, exerting a long-lasting destructive impact on well-being, quality of life, and educational and occupational functioning, and causing morbidity [ 23 , 26 , 27 ].…”
Section: Clinical Manifestations Of Long Covid Psychiatric Sequelaementioning
confidence: 99%
“…Notably, the relationship between psychiatric disorders/ symptoms and the COVID-19 disease is bidirectional. Patients with a pre-pandemic existing psychiatric disorder were found to be at increased risk for long COVID psychiatric sequelae [ 24 , 28 ]. Life changes and disruptions, restrictions, social isolations, economic loss, and threats of death during the COVID pandemic also create a huge and compound stressful environment where risk factors for psychiatric disorders are exacerbated [ 29 , 30 ].…”
Section: Clinical Manifestations Of Long Covid Psychiatric Sequelaementioning
confidence: 99%
“…Existing literature proposes that inflammatory mechanisms in COVID-19 infection could be responsible for an increase in depressive symptoms [30, 31]. This could certainly resonate with the association only being found for depression, and not for anxiety [32]. Although there was no evidence for the longitudinal association of stringency index with depressive symptoms in the ‘freedom’ period, the association was found for anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature proposes that inflammatory mechanisms in COVID-19 infection could be responsible for an increase in depressive symptoms [32,33]. This could certainly resonate with the association only being found for depression, and not for anxiety [34]. Although there was no evidence for the longitudinal association of stringency index with depressive symptoms in the "freedom" period, the association was found for anxiety symptoms.…”
Section: Plos Medicinementioning
confidence: 94%